Analysis Quality Control of White Tofu Products using The Six Sigma Method at UD Al Jaliil Tofu Factory in Jember Regency - Qurrotul‘ Aini; R. Abdoel Djamali (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
UD Al Jaliil is one of the white tofu producing agroindustry in Jember Regency. The challenge faced in maintaining quality is that defective products are still found. To deal with this problem, UD Al Jaliil needs to carry out quality control using the Six Sigma method. This study aims to 1) analyze the implementation of quality control at UD Al Jaliil using the Six Sigma method 2) determine the DPMO value and Sigma level of white tofu products 3) identify the factors that cause defective products so that efforts to improve the quality of white tofu can be determined. Quality control is carried out using the Six Sigma method. Six Sigma is a quality control method by reducing the level of defects through five DMAIC stages, namely Define, Measure, Analyze, Improve and Control. The results showed that the process at UD Al Jaliil had not been fully controlled properly because there were still processes that were outside the control limits. The DPMO value of 306,300 units/process means that in one million products produced there is a possibility of 306,300 defective products. The Sigma level of UD Al Jaliil is 2.0064 Sigma. And there are several factors that cause texture defects of white tofu, namely man, machine, method, material and environment factors.